KEPEMIMPINAN STRATEGIS KEPALA SEKOLAH DALAM MEMBANGUN CITRA SEKOLAH UNGGUL: STUDI KASUS DI SMA AL AULIA: Strategi Kepala Sekolah; Citra Sekolah; Sekolah Unggul; Kepemimpinan Pendidikan. - Rahmi, Sri; Na'im, Zaedun; Adawiyah; Rahmawati, Ima (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
The school principal holds a strategic role in building a superior school image, especially in addressing the challenges of 21st-century education. This study aims to describe the strategies employed by the principal in enhancing the school's image at SMA Al Aulia. A qualitative approach with a case study method was adopted. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that the principal implemented transformational leadership strategies, strengthened school culture, improved the quality of academic and non-academic services, and optimized public communication and the use of digital media. These strategies have proven effective in increasing public trust and reinforcing the school's positioning as a competitive educational institution. This study enriches the discourse on educational leadership and offers empirical contributions to models of school image development.